1993
DOI: 10.1042/bj2910523
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of mammalian cardiac AMP deaminase by protein kinase C-mediated phosphorylation

Abstract: Using AMP deaminase (AMP aminohydrolase; EC 3.5.4.6) purified from rabbit left-ventricular heart tissue, we report direct investigation of the potential for cardiac AMP deaminase activity to be regulated by kinase-mediated phosphorylation. Rabbit heart AMP deaminase served as a substrate for Ca2+/phospholipid-dependent protein kinase (protein kinase C; PKC) exclusively; no other mammalian protein kinase phosphorylated the enzyme. PKC-dependent AMP deaminase phosphorylation was rapid, linear with respect to tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The AMPD1 isoform is found almost exclusively in skeletal muscle, whereas the AMPD2 and AMPD3 isoforms are widely expressed in many tissues and cells (19,20), including mammalian brain (21,22). AMPD activity is highly regulated through interactions with other proteins (23)(24)(25), phosphorylation (26,27), and small molecules (10, 11, 28 -32). Regarding the latter, polyphosphates (32) and inositol (1,2,3,4,5,6)-hexakisphosphate (10) inhibit AMPD, whereas inositol (1,3,4,5)-tetrakisphosphate (Ins(1,3,4,5)P 4 ) modestly stimulates AMPD activity (11).…”
mentioning
confidence: 99%
“…The AMPD1 isoform is found almost exclusively in skeletal muscle, whereas the AMPD2 and AMPD3 isoforms are widely expressed in many tissues and cells (19,20), including mammalian brain (21,22). AMPD activity is highly regulated through interactions with other proteins (23)(24)(25), phosphorylation (26,27), and small molecules (10, 11, 28 -32). Regarding the latter, polyphosphates (32) and inositol (1,2,3,4,5,6)-hexakisphosphate (10) inhibit AMPD, whereas inositol (1,3,4,5)-tetrakisphosphate (Ins(1,3,4,5)P 4 ) modestly stimulates AMPD activity (11).…”
mentioning
confidence: 99%
“…AMPD can also be regulated via reversible protein phosphorylation by the Ca2+ and phospholipid-dependent protein kinase C (PKC) (Hu et al, 1991;Tovmasian et al, 1990;Thakkar et al, 1993). The enzyme also is inhibited by phosphoinositides (Sims et al, 1999).…”
Section: Enzymes Of Adenylate Energy Metabolismmentioning
confidence: 99%
“…Stimulation of a-adrenergic cascade and the protein kinase C activators were shown to decrease AMPD activity in experiments with rat cardiomyocytes subjected to metabolic poisoning. It was suggested that it may be modulated by phosphorylation-dependent reactions [2,31]. The endothelium represents a minor cell population in the heart, but its strategic location at vessel wall borders underlies its importance.…”
mentioning
confidence: 99%